Renewable nanocomposite layer-by-layer assembled catalytic interfaces for biosensing applications - Mantha, Saroja; Pedrosa, Valber de Albuquerque [UNESP]; Olsen, Eric V.; Davis, Virginia A.; Simonian, Aleksandr L. (American Chemical Society (ACS), 2010)
A novel, easily renewable nanocomposite interface based on layer-by-layer (LbL) assembled cationic/anionic layers of carbon nanotubes customized with biopolymers is reported. A simple approach is proposed to fabricate a nanoscale structure composed of alternating layers of oxidized multiwalled carbon nanotubes upon which is immobilized either the cationic enzyme organophosphorus hydrolase (OPH; MWNT−OPH) or the anionic DNA (MWNT−DNA). The presence of carbon nanotubes with large surface area, high aspect ratio and excellent conductivity provides reliable immobilization of enzyme at the interface and promotes better electron transfer rates. The oxidized MWNTs were characterized by thermogravimetric analysis and Raman spectroscopy. Fourier transform infrared spectroscopy showed the surface functionalization of the MWNTs and successful immobilization of OPH on the MWNTs. Scanning electron microscopy images revealed that MWNTs were shortened during sonication and that LbL of the MWNT/biopolymer conjugates resulted in a continuous surface with a layered structure. The catalytic activity of the biopolymer layers was characterized using absorption spectroscopy and electrochemical analysis. Experimental results show that this approach yields an easily fabricated catalytic multilayer with well-defined structures and properties for biosensing applications whose interface can be reactivated via a simple procedure. In addition, this approach results in a biosensor with excellent sensitivity, a reliable calibration profile, and stable electrochemical response.